Accountability and Transparency in the Management of Special Autonomy Funds in Asmat Regency: Implications for Public Trust - Agas, Syamsul (KnE Social Sciences, 2025)
This study explores how accountability and transparency influence public trust in the management of special autonomy (Otsus) funds in Asmat Regency, South Papua Province, Indonesia. This was a qualitative study using in-depth interviews and field observations with 30 stakeholders, including government officials, community leaders, and citizens across five districts. Key findings reveal persistent gaps in financial accountability, limited transparency mechanisms, and a direct correlation between poor governance practices and declining public trust. The study underscores the need for institutional reforms to improve reporting systems, community access to information, and participatory monitoring. These improvements are essential to strengthen legitimacy, governance credibility, and social inclusion in Papua’s development.